2021
DOI: 10.21203/rs.3.rs-222495/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Camel and Small Ruminant Based Pastoralism in Ethiopia: Recent Trends and Future Prospects

Abstract: In Ethiopia, camel and shoat production are common pastoralism practices in three major pastoralist regions of Afar, Somali, and Borena. This review was aimed to indicate the recent trend and future prospect of camel and small ruminant production and the possible modifiers and the pros and cons of the practices in the pastoral area of Ethiopia. Data were organized and estimated from different researches conducted in each year. Data were organized in terms of the number of camel and shoat per household each yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Additionally, there are economic advantages from multispecies pastoralism because income diversification allows herders to better cope with economic, political and ecological instabilities. In some case studies, for example, it was shown that many households in the three most important Ethiopian pastoralist communities (the Afar in the northeast, the Borana in the south and the Somali in the east and southeast) have already diversified their income sources from livestock, to the extent that there are differences in household income depending on the extent of their engagement in multispecies herding 38,74 . Marketing and customer preferences for different goat and camel products vary greatly from one region to another, between rural and urban communities with different socioeconomic standards, and between different ethnic groups, and are changing over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there are economic advantages from multispecies pastoralism because income diversification allows herders to better cope with economic, political and ecological instabilities. In some case studies, for example, it was shown that many households in the three most important Ethiopian pastoralist communities (the Afar in the northeast, the Borana in the south and the Somali in the east and southeast) have already diversified their income sources from livestock, to the extent that there are differences in household income depending on the extent of their engagement in multispecies herding 38,74 . Marketing and customer preferences for different goat and camel products vary greatly from one region to another, between rural and urban communities with different socioeconomic standards, and between different ethnic groups, and are changing over time.…”
Section: Discussionmentioning
confidence: 99%
“…There have been multiple reports documenting where pastoralist communities in drylands of NSSA (for example, Wodaâbe in Niger, Massaï in Kenya, Borana in Ethiopia, Nuer in South Sudan, and Fulani in West Africa) have adjusted their livestock composition in response to environmental extremes and changing ecological conditions, mostly by shifts from cattle to small ruminants (mainly goat) and/or camels [31][32][33][34] . Browsers (that is, camels and goats) in some pastoralist communities are preferred over grazers (that is, cattle) due to their greater climate resilience, resulting from their higher tolerance to drought and feed scarcity, as well as their capacity to produce milk and meat in all seasons 33,[35][36][37][38] . The shifting preference for browsers (that is, favouring camels and goats over cattle) due to recent climate variability/change, and associated feed and water shortage was confirmed by over 71.5% of the interviewed households from a survey of the Borana community from Isiolo County, northern Kenya 39 .…”
mentioning
confidence: 99%